Transforming Dental Mould Waste (DMW) Into High Purity Calcium Source By Chromium Removal Through Alkaline Caustic Leaching (ACL) Using Ultrasonic Technology - Mohamad Yusoff, Nurulaini (Universiti Sains Malaysia, 2022)
The dumping of dental mould waste (DMW) into landfill is increasing every year and IPPT Bertam, Penang also have a lot of DMW that need to dump every month. As we know, DMW is recognised as gypsum, which has high calcium content. Thus, recycling of DMW seems as a sustainable approach to obtain alternative source of calcium, which can further be used in bioceramics applications. This calcium source can then be used as the main precursor in producing akermanite bioceramics. This study can be divided into two parts: (1) synthesis of calcium hydroxide using different frequencies of ultrasonic technology (i.e. 40, 132, 360 kHz) by removing the chromium content in DMW (2) fabrication of akermanite bioceramics using calcium source from DMW sintered at three temperatures (1200,1225 and 1250°C). The results obtained showed that 40kHz is the most efficient frequency in removing chromium content from DMW, resulting in higher purity of calcium hydroxide obtained. This finding supports the theory where lower ultrasonic frequency is commonly used for coarser powders. Meanwhile, the optimum sintering temperature in producing akermanite ceramics is determined to be at 1225°C.